1946
DOI: 10.1097/00000658-194610000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Gastrectomy in Selected Cases of Gastric Ulcer

Abstract: CHRONIC BENIGN ULCERS high on the lesser curvature of the stomach and those juxta-esophageal in position have always presented technical problems in their surgical management. A multiplicity of procedures has been advocated. At first, these operations were designed to relieve the gastric retention secondary to a reflex pylorospasm. However, gastrojejunostomy, usually without the local excision of the lesion, even though it relieves the obstruction, has been found to be an unreliable and ineffectual operation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1947
1947
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Others [3,4] also describe a higher incidence among women and this corresponds to reports of an increasing incidence of perforated gastric ulceration in women while the incidence in men is tending to fall [5,6]. In one series, however [7], the HGU patients were mostly men. The mean age of our patients was 66 years and 20% of them were older than 75 years.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Others [3,4] also describe a higher incidence among women and this corresponds to reports of an increasing incidence of perforated gastric ulceration in women while the incidence in men is tending to fall [5,6]. In one series, however [7], the HGU patients were mostly men. The mean age of our patients was 66 years and 20% of them were older than 75 years.…”
Section: Discussionsupporting
confidence: 61%
“…We found that almost 40% of the ulcers were deeply penetrating into surrounding structures and the figure may be as high as 100% [7]. The importance of this will be discussed later.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Gastric ulcer is characterized by certain features which are lacking in duodenal ulcer and which exert an important influence upon the -management of the disease. These several peculiarities may be' summarized briefly as follows: (i) the existence of ulcer, its exact location, size and other characteristics can be demonstrated by roentgenologic examinations and/or gastroscopy in a high percentage of cases; (2) the response to treatment may be very accurately followed and recorded by these same methods; (3) it is often closely mimicked by primary ulcerating carcinoma; (4) carcinomatous degeneration may occur as a late complication of an originally benign chr-onic gastric ulcer; (5) surgical intervention is required in a larger percentage( of cases than in the case of duodenal ulcer; (6) practically all surgical procedures, including the simpler ones, will substantially reduce the gastric acidity; (7) the clinical results of operative treatment are better than in duodenal ulcer and (8) anastomotic ulcer is a rare complication following gastroenteric anastomoses for gastric ulcer.…”
mentioning
confidence: 99%